Cognitive Flexibility and Sustained Attention: See something, say something (even when it's not there). (September 2014) - Figueroa, Ivonne J.; Youmans, Robert J.; Shaw, Tyler H.
Researchers investigating the relationship between individual differences and sustained attention tasks do not clearly find marked traits and abilities that are predictive of vigilant performance. Yet, this important research is applicable to tasks like driving, TSA monitoring, Air Traffic Control, and even for the Department of Homeland Security's civilian campaign, "See something, say something." In this paper, we take an individual differences approach to uncover the relationship between cognitive flexibility and sustained attention. Twenty-nine undergraduate students from George Mason University participated in this study for course credit. The Youmans Cognitive Flexibility Puzzle (Gonzalez, Figueroa, Bellows, Rhodes, & Youmans, 2013) was used to assess cognitive flexibility, and a modified version the Air Traffic Controller (ATC) task (Hitchcock, Warm, Matthews, Dember, Shear, Tripp et al., 2003) measured sustained attention. Mixed ANOVAs were used to analyze performance on the ATC task ( hits, false alarms, reaction times ). Highly flexible individuals were faster to respond despite missing signals and committing errors. Implications are discussed.